2011
DOI: 10.1002/dc.21389
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Her2/neu, estrogen receptor, and progesterone receptor testing by immunohistochemistry on cell block of FNA and serous effusions from patients with primary and metastatic breast carcinoma

Abstract: The prognostic and predictive value of Her2/neu and the hormone receptors in patient with primary or metastatic breast cancer is essential for a favorable outcome of treatment. We have been experiencing increasing requests to test cytologic specimens for these markers in patients with metastatic breast carcinoma. A recent study threw some doubts on the validity of such testing using cell blocks. In this study we compared our immunohistochemical Her2/neu, ER and PR testing performed on 42 formalin-fixed, paraff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 60 publications
(61 reference statements)
4
78
1
1
Order By: Relevance
“…However the newer techniques utilize methanol-based fixation, which interfere with immunohistochemical analysis especially for ER, PR, MIB 1 and Her 2 neu [9][10][11]. However this issue may be overcome by formalin pre-fixation prior to Cellient [7].…”
Section: Discussionmentioning
confidence: 99%
“…However the newer techniques utilize methanol-based fixation, which interfere with immunohistochemical analysis especially for ER, PR, MIB 1 and Her 2 neu [9][10][11]. However this issue may be overcome by formalin pre-fixation prior to Cellient [7].…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary study at our institution, we encountered difficulties in scoring the HER2 status by IHC methods using liquid‐based cytological specimens stored in ThinPrep PreservCyt Solution (Hologic) and found a low concordance rate with the corresponding histological specimens (data not shown). According to the reasoning mentioned above, formalin‐fixed CBs are recommended for HER2 IHC staining 2, 3. However, discordant results are reported between formalin‐fixed CBs and tissue specimens.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study has reported that formalin‐fixed cell blocks (CBs) from primary or metastatic breast carcinoma showed 100% correlation with their corresponding histological sections3 and the other study has reported that CBs are reliable for IHC detection of HER2 16…”
mentioning
confidence: 99%
“…Neutral buffered formalin is the only fixative recommended by manufacturers of her2 testing kits such as HercepTest 12 , but fnas and pleural effusions are often fixed in ethanol, and concerns have been expressed that that approach may have a negative impact on the reliability of her2 testing; nonspecific (false-positive) ihc staining for her2 protein overexpression has been observed in some studies involving ethanol-fixed samples [13][14][15] . Conversely, formalin fixation of fnas appears to improve the reliability of subsequent her2 testing; concordance rates of up to 100% have been reported between formalin-fixed fnas or serous effusions and matched formalin-fixed tissue sections 9 .…”
Section: 21mentioning
confidence: 99%
“…Methods currently used to test her2 status were developed and optimized for use with formalin-fixed, paraffin-embedded breast tissue specimens derived from surgical excisions 9 . However, tissue handling and fixation methods used with non-excisional samples may vary from those used with larger tissue samples.…”
Section: Introductionmentioning
confidence: 99%